2009
DOI: 10.1002/pssc.200881443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dislocation trails on gold diffusion in Si

Abstract: Gold diffusion in plastically deformed Si containing dislocation trails has been carried out at temperatures 700 and 750 °C. The substitutional gold depth profile has been studied by successive sample etching and DLTS profiling. It is observed that the gold concentration in plastically deformed Si is about 10 times higher than that in defect‐free Si. Moreover, it is at least 10 times higher than that estimated for the dislocation density revealed in the samples under study. It is concluded that the observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Generally, the transition between interstitial gold and substitutional in defect‐free silicon was described to occur via kick out mechanism generating self‐interstitials 18. In defect free silicon, concentration of Au s was found to be smaller compared with that in silicon samples containing more vacancy or vacancy related complexes, indicating that vacancies could lead to increased concentration of Au s via dissociative mechanism 19. It is well known that gold has two deep levels in silicon.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the transition between interstitial gold and substitutional in defect‐free silicon was described to occur via kick out mechanism generating self‐interstitials 18. In defect free silicon, concentration of Au s was found to be smaller compared with that in silicon samples containing more vacancy or vacancy related complexes, indicating that vacancies could lead to increased concentration of Au s via dissociative mechanism 19. It is well known that gold has two deep levels in silicon.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, it was shown that dislocations trails rather efficiently interacted with transition metals, inducing an increase in the impurity concentration (Au) compared to that in a defect free crystal and intensifying precipitation (Fe). In this case, the recombination activity of these dislocation trails is substantially altered [7][8][9][10]. In this context, demand has arisen for more thorough studies of the interaction of these defects with metal atoms and the influence of such interaction on the electrical properties of extended defects.…”
Section: Introductionmentioning
confidence: 97%
“…It was well established that dislocations gliding in Si at 600-800 C generate some defects in the slip planes, so called the dislocation trails (DTs). [1][2][3][4][5][6][7][8][9][10][11][12] DTs can be revealed by the selective chemical etching [1] and by the electron-beam-induced current (EBIC) and laser-beam-induced current (LBIC) methods. [2][3][4][5][6][8][9][10][11] Due to their electrical activity, DTs introduce deep levels in the bandgap [3,5,12] and affect the electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%